Pengembangan Keahlian Penggunaan Microsoft Excel bagi Instruktur Pelatihan TIK Nasional bagi Disabilitas - Tri Sugihartono; Rahmat Sulaiman; Sarwindah Sarwindah (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
Bakti Kominfo has tasks in the ICT section, namely building IT network infrastructure in disadvantaged areas. In addition, BAKTI Kominfo also has a role in developing human resources who have expertise in the IT field and keep up with the current developments, namely the Digital world. Therefore, BAKTI Kominfo conducts training for ICT teachers to provide insight as a provision to guide students with disabilities to take part in National ICT Training and Competitions. One of the training materials is Excel. In this activity in collaboration with ISB Atma Luhur to train ICT teachers with Microsoft Excel material. This training lasts for 3 consecutive days using Zoom Meeting. In the conditions of the Covid-19 Pandemic, this did not discourage us from always innovating in making and holding training courses to develop skills from ICT teacher teacher resources to assist students with disabilities. The goal is to capture the hidden competences and talents of students with disabilities. With this training activity, the ability of ICT teachers to use Microsoft Excel 2016. And from the training participants suggested to always innovate in making training training similar to other materials and to always be accompanied during training and even after training.